1993
DOI: 10.1111/j.1540-8159.1993.tb01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Rate Pacing Controlled by Right Ventricular Preejection Interval for Severe Refractory Orthostatic Hypotension

Abstract: A 72-year-old African-American man with frequent recurrent syncope was found to have severe refractory orthostatic hypotension with concomitant supine hypertension. Pharmacotherapy was successful in controlling his supine hypertension but was unable to resolve his severe orthostatic hypotension. Temporary fixed rate tachypacing was only minimally effective in preventing syncope during upright tilt, while variable rate pacing based on degree of blood pressure fall was far superior. Following these observations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As seen in Table 5, however, the stroke volume also drops with tilting and pacing requiring even faster pacing rates. Some of the studies that showed a benefit with tachypacing paced at rates of 125 bpm [6]. With faster heart rates,however,the stroke volume may be lower due to reduced diastolic filling time thereby making the strategy potentially self defeating.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As seen in Table 5, however, the stroke volume also drops with tilting and pacing requiring even faster pacing rates. Some of the studies that showed a benefit with tachypacing paced at rates of 125 bpm [6]. With faster heart rates,however,the stroke volume may be lower due to reduced diastolic filling time thereby making the strategy potentially self defeating.…”
Section: Discussionmentioning
confidence: 97%
“…Abe et al [1] describe two cases in which tachypacing at 100 beats per minute prevented syncope. Grubb et al [6] describe another case of an elderly man with severe refractory orthostatic hypotension and supine hypertension who benefited from adaptive tachypacing. Other authors have reported similar findings [5,7,12].…”
Section: Introductionmentioning
confidence: 98%
“…This patient could not appropriately respond to fall the BP at the time of postural change so syncope or presyncopal state is exhibited. There have been some reports of attempting atrial-pacing therapy to increase heart rate and thereby increase cardiac output in order to improve hypotension in OH patients [3][4][5][6]. A mechanism of OH improvement by atrial overdrive pacing has not been made clear.…”
Section: Discussionmentioning
confidence: 99%
“…Severe OH patients with chronotropic incompetence have no adequate response of HR, when the BP falls during postural change. There have been a few reports of cardiac pacing therapy effectively providing good clinical result for drug-refractory OH [3][4][5][6]. In the small group study, rate response pacing is effective to keep BP and HR during postural change for OH patients with chronotropic incompetence.…”
Section: Introductionmentioning
confidence: 99%
“…The development of novel sensor technologies that would permit either direct or indirect measurement of blood pressure would allow for the onset of pacing at a much earlier point in the syncopal event providing a greater likelihood of altering or aborting its progression. Early reports of sensors using right ventricular or transthoracic impedance have been encouraging [27], as have other systems still in development [28].…”
Section: Clinical Trialsmentioning
confidence: 99%